Dr. Lilith Ritter and the Femme Fatale Archetype in Nightmare Alley (2021): A Sociological Perspective - Azizah Nur Rahmadhani; Ali Mustofa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how Dr. Lilith Ritter in Guillermo del Toro's Nightmare Alley (2021) subverts the traditional femme fatale archetype through intellectual rather than sexual power. Applying Yvonne Tasker's (1993) sociological framework of the "female hero" from Spectacular Bodies: Gender, Genre, and the Action Cinema, this qualitative film analysis investigates five key scenes featuring Ritter's interactions with the male protagonist Stanton Carlisle. The findings reveal that Ritter replaces sexual seduction with three forms of professional power: intellectual authority (using psychoanalytic tools to deconstruct masculine performance), institutional status (controlling conversations and material evidence as a psychiatrist), and psychological opacity (remaining unreadable while accurately reading others). Rather than embodying male anxiety, Ritter critiques patriarchal systems by exposing masculine fragility through competence. This research extends Tasker's sociological theory to the neo-noir genre, offering an alternative reading of the femme fatale as a critique of systemic gender inequality rather than a symbol of male insecurity.